On thermal nucleation of quark matter in compact stars - Mintz, Bruno W.; Fraga, E. S.; Schaffner-Bielich, Jürgen; Pagliara, Giuseppe (Journal of physics. G, Nuclear and particle physics, 2010)
The possibility of a hadron-quark phase transition in extreme astrophysical phenomena such as the collapse of a supernova is motivated from our present knowledge of the high-energy nuclear and quark-matter equations of state. Both the density and the temperature attainable in such extreme processes are possibly high enough to trigger a chiral phase transition. However, the time scales involved are an important issue. Even if the physical conditions for the phase transition are favorable (for a system in equilibrium), there may not be enough time for the dynamical process of phase conversion to be completed. We analyze the relevant time scales for the phase conversion via thermal nucleation of bubbles of quark matter and compare them to the typical astrophysical time scale, in order to verify the feasibility of the scenario of hadron-quark phase conversion during, for example, the core-collapse of a supernova.
Gesehen am 26.04.2023